Lifestyle Related Behavioral Changes Owing to the Global Pandemic among COVID-19 Positive Physicians Serving in a COVID Dedicated Tertiary Care Hospital - Rahman, Farzana; Sufrin, Sumaira; Rashed, Asif (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: The COVID-19 pandemic continues to pose significant challenges and has had a global effect on people’s lifestyle. The impact of measures taken to contain COVID-19 on lifestyle related behavior is undefined among physicians with COVID-19 positive serving in a corona dedicated health center. Objective: The current study was undertaken to assess the impact of COVID-19 on life style related behaviors among physicians with COVID-19 including all human sciences related to lifestyle, dietary habits physical activity and behavioral studies. Methods: The study is a descriptive type of cross-sectional web-based survey. The survey was conducted from March to May, 2021 among 61 COVID-19 infected physicians working at Mugda Medical College Hospital through a validated semi-structured questionnaire incorporated with GAD-7 scale using Google online survey platform. The sample was selected purposively and collected data were analyzed by SPSS-21 version. The P-value was two sided and values <0.05 were regarded as statistically significant. Results: A total of 61 responses 70% were male and mean age was 35.33±12.5 SD. An improvement in healthy meal consumption pattern and a restriction of unhealthy food items were observed. 48.6% respondents had weight gained with an increase in daily screen time especially found among men. 3.5% of smokers decided to quit smoking. Physicians group aged 31-40 years resulted highly significant adherence in the consumption of carbohydrates and minerals when compared to the elderly physicians (P<0.001). Quarantine induced stress and anxiety showed in nearly one-fourth of the participants. Physicians reported that their quality of life (QoL) had adversely affected after the pandemic struck. Conclusion: We obtained novel data for the first time on COVID-19 positive physicians’ lifestyle and related behavioral changes. As the COVID-19 pandemic is ongoing, our data need to be investigated in future more extensive studies to develop interventions to mitigate the negative lifestyle behaviors to deal with the pandemic situation as well as future crises. J Shaheed Suhrawardy Med Coll 2021; 13(2): 117-125